Exploring the Experiences of Tour and Travel Alumni in Job Hunting - Imawaty Daiki (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Becoming an alumnus marks the beginning of life for students in their pursuit of employment. Career orientation is the primary goal for graduates to develop the knowledge and skills they have acquired during their studies, although alumni often face challenges in finding jobs. Competition and problems in the job market are common occurrences. Issues frequently arise in the quest for stable income without relevant solutions. Moreover, companies sometimes view alumni as lacking sufficient experience in their fields, thus limiting their opportunities to achieve their career goals.This study aims to explore the experiences of Tour and Travel alumni in seeking employment within the tourism industry, both in formal and informal sectors. The research focuses on understanding the challenges faced by alumni, the relevance of the skills acquired during their studies to labor market demands, and the strategies used by alumni in their efforts to secure suitable employment. This study employs a qualitative method, conducting interviews with several alumni to gain insights into the challenges and strategies they encounter as they enter the workforce. The results of the study revealed that most alumni face various challenges, such as intense competition in the tourism industry, a lack of practical work experience during their studies, and market dynamics that have shifted due to technological advancements and the impact of the pandemic. In addition to technical skills like travel management and customer service, non-technical skills such as communication, negotiation, critical thinking, and adaptability are highly sought after by companies. Some alumni recognize the need to develop networks and participate in additional training or certifications to enhance their competitiveness in the job market. While some alumni struggle to find jobs in the tourism sector, many successfully find employment in other fields that require similar skills, such as hospitality, logistics, and event management. This research provides recommendations for educational institutions to strengthen internship programs and increase collaboration with the industry. Additionally, alumni are advised to continuously update their skills and leverage digital opportunities in their job search.